Pharmacodynamics of Cefepime Combined with the Novel Extended-Spectrum-β-Lactamase (ESBL) Inhibitor Enmetazobactam for Murine Pneumonia Caused by ESBL-Producing Klebsiella pneumoniae - Johnson, Adam (Antimicrob Agents Chemother, 2020)
Klebsiella pneumoniae strains that produce extended-spectrum beta lactamases (ESBLs) are a persistent public health threat. There are relatively few therapeutic options, and there is undue reliance on carbapenems. Alternative therapeutic options are urgently required. A combination of cefepime and the novel beta lactamase inhibitor enmetazobactam is being developed for the treatment of serious infections caused by ESBL-producing organisms. The pharmacokinetics-pharmacodynamics (PK-PD) of cefepime-enmetazobactam against ESBL-producing K. pneumoniae was studied in a neutropenic murine pneumonia model. Dose-ranging studies were performed. Dose fractionation studies were performed to define the relevant PD index for the inhibitor. The partitioning of cefepime and enmetazobactam into the lung was determined by comparing the area under the concentration-time curve (AUC) in plasma and epithelial lining fluid. The magnitude of drug exposure for cefepime-enmetazobactam required for logarithmic killing in the lung was defined using 3 ESBL-producing strains. Cefepime, given as 100 mg/kg of body weight every 8 h intravenously (q8h i.v.), had minimal antimicrobial effect. When this background regimen of cefepime was combined with enmetazobactam, a half-maximal effect was induced with enmetazobactam at 4.71 mg/kg q8h i.v. The dose fractionation study suggested both fT > threshold and fAUC:MIC are relevant PD indices. The AUC(ELF):AUC(plasma) ratio for cefepime and enmetazobactam was 73.4% and 61.5%, respectively. A ≥2-log kill in the lung was achieved with a plasma and ELF cefepime fT > MIC of ≥20% and enmetazobactam fT > 2 mg/liter of ≥20% of the dosing interval. These data and analyses provide the underpinning evidence for the combined use of cefepime and enmetazobactam for nosocomial pneumonia.